Insight into proteomic investigations of Neisseria meningitidis serogroup C strain L91543 from analysis of its genome sequence - Karlyshev, A.V.; Snyder, Lori A.S.; McFadden, Johnjoe; Griffin, R. (Oxford University Press, 2015)
Here, we describe the draft sequence of a virulent isolate of Neisseria meningitidis strain L91543, belonging to serogroup C. The findings from previous proteomic and metabolomic studies of this strain can now be further interpreted with genomic analysis. Comparative analysis of the genome sequence revealed close similarity and localized synteny with the genome sequence of N. meningitidis serogroup C strain, FAM18. Polymorphisms were identified in the signal peptide sequence of factor H binding protein, a target for new meningococcal vaccines, which may result in its inefficient translocation across the cytoplasmic membrane affecting its processing (lipidation and cleavage of the signal peptide) and transportation to the outer membrane in strain L91543. This would explain the unusual proteomic data for factor H binding protein for this strain. NadA, another target for new vaccines, and the MtrR regulator, which controls expression of NadA, both contain SNPs between strains L91543 and FAM18. The genome sequence data were generated using Ion Torrent PGM sequencing, assembled into 50 contigs with 64× coverage and annotated with 2262 genes, 14 rRNAs and 56 tRNAs. The availability of the genome of N. meningitidis strain L91543 will aid our understanding of the proteome of this organism, importantly its vaccine antigens.